Manipulation and Sorting of Cell-Laden Hydrogel Microcapsules Within Microfluidic Environment - Dhingra, Karan (Université d'Ottawa / University of Ottawa, 2019)
Encapsulating cells within semi-permeable hydrogel material has been shown to boost the therapeutic effectiveness of stem cell therapy in certain applications. Cell encapsulation promotes high retention and engraftment rates, and protects against attack from the immune system of the host, as these are challenges often seen in utilizing stem cells in suspension alone. Leveraging droplet-based microfluidics has yielded a platform capable of producing monodispersed microcapsules embedded with cells at high throughput, typically achieved by mixing an aqueous hydrogel solution that contains cells with an immiscible liquid (oil) in a flow focusing geometry. However, encapsulation using microfluidics results in randomized generation of empty and cell-laden microcapsules, following Poisson statistics, raising the need to institute a successful sorting mechanism, thereby increasing occupancy and ultimately purifying the desired sample. In this thesis we propose a sorting strategy by combining two conceptual mechanisms of electrophoresis (EP) and deterministic lateral displacement (DLD). Different varieties of microcapsules were characterized for EP and DLD respectively. Leveraging these differences was used in a device combining both of the concepts towards sorting of empty and cell-laden microcapsules.
Keywords: Microfluidics; Stem cell; Biomedical; Phyisics